2012
DOI: 10.1029/2011jb008911
|View full text |Cite
|
Sign up to set email alerts
|

Control of pore fluid pressure diffusion on fault failure mode: Insights from the 2009 L'Aquila seismic sequence

Abstract: [1] The M W 6.13 L'Aquila earthquake ruptured the Paganica fault on 2009/04/06 at 01:32 UTC, and started a strong sequence of aftershocks. For the first four days, the region north of the hypocenter of the main quake was shaken by three large events (M W $ 5.0) that ruptured different patches of the Monti della Laga fault (hereafter "Campotosto"). In our hypothesis, these aftershocks were induced by a dramatic reduction in the fault's shear strength due to a pulse of pore fluid pressure released after the L'Aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 60 publications
12
81
0
Order By: Relevance
“…Starting from 2010, the recrudescent seismicity featured peculiar patterns of migration and change in the magnitude frequency distribution of earthquakes [ De Gori et al , ] evocative of critically stressed patches. Furthermore, fluid migration has been evoked as an explanation for seismicity rate changes observed in the Apennines [ Lombardi et al , ; Chiarabba et al , ] and propagation of seismicity and swarms during normal faulting seismic sequences [ Antonioli et al , ; Chiarabba et al , ; Malagnini et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from 2010, the recrudescent seismicity featured peculiar patterns of migration and change in the magnitude frequency distribution of earthquakes [ De Gori et al , ] evocative of critically stressed patches. Furthermore, fluid migration has been evoked as an explanation for seismicity rate changes observed in the Apennines [ Lombardi et al , ; Chiarabba et al , ] and propagation of seismicity and swarms during normal faulting seismic sequences [ Antonioli et al , ; Chiarabba et al , ; Malagnini et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show that rift maturation is a highly dynamic process, both spatially and temporally. Further, the rifting process can be highly infl uenced by fl uid fl ux through fault systems, which can create elevated pore fl uid pressures, modify the local stress fi eld by reducing the effective normal stress, and hence facilitate fault slip and strain accumulation rates (e.g., Hubbert and Rubey, 1959;Malagnini et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fluids can play an important role in seismogenic processes, as pore pressure increases tend to reduce the strength of the fault and can trigger earthquake activity (Di Luccio et al 2010;Malagnini et al 2012). Geological data for the study area reveal the presence of gas and brines hosted in Cretaceous and Miocene terrains as well as evaporites of the Mesozoic-Triassic sequence which may maintain high fluid pressure at depth due to their low permeability (Ventura and Di Giovambattista 2012).…”
Section: Fluid Pressure Estimatementioning
confidence: 99%
“…An increment of pore fluid pressure was also found for the April 2009 L'Aquila seismic activity by Di Luccio et al (2010), who accounted the pore pressure diffusion as the main mechanism controlling the space-time distribution of aftershocks. Malagnini et al (2012) showed that a secondary structure north of L'Aquila was activated after the April 6, 2009 main shock, due to the effects of the migrating pore fluid pressure field, which dominated the strength of the structure for at least six days and led it to multiple failures. Ventura and Di Giovambattista (2012), analyzing the spatial and temporal evolution of the MayJune 2012 Emilia seismic sequence, concluded that the earthquakes interested two buried coalescing thrusts of Northern Apennines which were activated by the presence of compressive regime and suprahydrostatic pore pressure.…”
Section: Introductionmentioning
confidence: 99%